Thermomechanical characterization and durability of adobes reinforced with millet waste fibers (sorghum bicolor). (December 2020) - Babé, Colbert; Kidmo, Dieudonné Kaoga; Tom, Ahmat; Mvondo, Rachel Raïssa Ngono; Boum, Raphaël Belinga Essama; Djongyang, Noël
Highlights: Durability, thermal and mechanical characteristics of adobes are investigated. Mechanical properties of adobes reinforced with 2 % of fibers are improved. Adobe bricks reinforced with fibers are less eroded than raw adobe. Adobe bricks reinforced with fibers showed better water resistance than raw adobe Thermal conductivity of adobe bricks decreases with increasing fibers. Abstract: Artisans in the Sudano-Sahelian zone of Cameroon make abundant use of adobes formulated from red millet fibers for the construction of houses. However, scientific data are missing in the literature to provide necessary information for the understanding of thermomechanical characteristics and durability of these materials. Adobe bricks used in this paper are formulated from the soil with 0, 1, 2, 3, and 4 % of millet waste. The samples are characterized by geotechnical, mechanical, thermal, and durability laboratory tests. Experimental measurements of mechanical and thermal characteristics show that millet fibers can contribute to the improvement of compressive strength and thermal conductivity by 38 and 23 % corresponding respectively to the incorporation of 2 and 4 % of millet fibers. Moreover, to understand the durability of the samples, the assessment of the behavior of adobe bricks exposed to water and friction (abrasion) shows that the incorporation of 2–4 % of millet fibers in the clay matrices, enabled us to obtain more resistant composites compared to the pure matrix. As a result, millet fibers, by their good adhesion to the clay matrix, act as reinforcement by contributing to the improvement of the thermomechanical characteristics and the durability of adobe bricks. Thus, adobe bricks reinforced with millet fibers can be used without damage, and cheap as building materials with a contribution to thermal comfort.